THE EFFECT OF CAPITAL INTENSITY, INDEPENDENT COMMISSIONERS, AND POLITICAL CONNECTIONS ON TAX AVOIDANCE - Peni Maharani Artiningsih; Djoko Wahyudi (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
The purpose of this study was to determine the effect of capital intensity, independent commissioners, and political connections on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2020. The independent variables used included capital intensity, independent commissioners, and political connections while the dependent variable is tax avoidance. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2020 as many as 175 companies. The sample used in this study were manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2020. Data collection using purposive sampling method. The data needed in this study was obtained from the annual published financial report data published by the IDX. The data analysis method used to test the hypothesis is multiple linear regression analysis. The results showed that independent commissioners had a significant positive effect on tax avoidance. Meanwhile, capital intensity and political connections have no significant effect on tax avoidance.